Enhancing Business Process Management (BPM) sustainability in the agriculture sector through precision agriculture, IoT, and UAV technologies - Rodzoan, Muhammad Asyraf; Shah, Asadullah (IEEE, 2025)
Agriculture is at the forefront of arguments over global sustainability given that it has a significant impact on resources such land, water, and energy. The significant contributions of business process management, or BPM, to agricultural sustainability is investigated in this article. The agriculture sector may increase operational efficiency, decrease resource waste, and improve sustainability results by integrating BPM with cutting-edge technologies like IoT and UAVs, along with process optimization methodologies. This study addresses the consequences of BPM-driven sustainability, with an emphasis on crop production, resource management, and environmental protection. It does this by using case examples and a review of recent literature. Furthermore, we suggest a paradigm for implementing BPM in agriculture that prioritizes stakeholder engagement and ongoing improvement.